An Approach for Differential Diagnosis of Breast Tumors by ctDNA Methylation Sequencing - Xianyu Zhang; Yanling Yin; Zhujia Ye; Xingda Zhang; Wei Wei; Yi Hao; Liuhong Zeng; Ting Yang; Dalin Li; Jun Wang; Dezhi Zhao; Yanbo Chen; et al. (Cancer Medicine, 2025)
ABSTRACT Background Breast ultrasonography and mammography remain predominant in breast tumor evaluations, yet they often result in false positives, particularly for tumors classified as BI‐RADS 4a or those no more than 10 mm, which are not ideal for core needle biopsy (CNB). Early‐stage breast cancer detection via circulating tumor DNA (ctDNA) methylation holds potential to bridge these diagnostic gaps. Methods We curated a breast cancer‐specific panel by harnessing methylation profiles from in‐house and public databases. Leveraging breast tissue‐plasma‐leukocyte samples, we identified breast cancer‐specific markers, culminating in a 103‐marker methylation model which underwent rigorous validation in two independent cohorts. To assess its performance, we compared it against the accuracy of ultrasonography, mammography, and CNB. Results The 103‐marker model exhibited remarkable proficiency in discerning benign from malignant breast tumors in plasma, with AUCs of 0.838, 0.838 and 0.823 in the validation set and two independent test sets, respectively. In BI‐RADS 4a breast cancer, when compared to ultrasonography or mammography, the model augmented breast cancer diagnostic accuracy by 40.58% and 25.49%, separately. Retrospective analyses suggested that our model achieved a sensitivity of 66.67% (4/6) and a specificity of 80.36% (45/56) for surgical patients in the BI‐RADS 4a category with tumors ≤ 10 mm, who did not undergo CNB, potentially sparing 45 benign patients from overtreatment. Notably, significant differences emerged in cancer scores between DCIS and invasive ductal carcinoma (p < 0.05). Higher cancer scores correlated with a more unfavorable prognosis (p < 0.05). Conclusions The 103‐marker methylation model demonstrates impressive performance in distinguishing between malignant and benign tumors, facilitating precise early diagnosis of BC, and holds promise as a prognostic tool.